Relevance, Impartiality, Welfare and Consent: Principles of an Animal-Centered Research Ethics - Mancini, Clara; Nannoni, Eleonora (Frontiers in Animal Science, 2022)
The principles of Replacement, Reduction and Refinement (3Rs) were developed to address the ethical dilemma that arises from the use of animals, without their consent, in procedures that may harm them but that are deemed necessary to achieve a greater good. While aiming to protect animals, the 3Rs are underpinned by a process-centered ethical perspective which regards them as instruments in a scientific apparatus. This paper explores the applicability of an animal-centered ethics to animal research, whereby animals would be regarded as autonomous subjects, legitimate stakeholders in and contributors to a research process, with their own interests and capable of consenting and dissenting to their involvement. This perspective derives from the ethical stance taken within the field of Animal-Computer Interaction (ACI), where researchers acknowledge that an animal-centered approach is essential to ensuring the best research outcomes. We propose the ethical principles of relevance, impartiality, welfare and consent, and a scoring system to help researchers and delegated authorities assess the extent to which a research procedure aligns with them. This could help researchers determine when being involved in research is indeed in an animal's best interests, when a procedure could be adjusted to increase its ethical standard or when the use of non-animal methods is more urgently advisable. We argue that the proposed principles should complement the 3Rs within an integrated ethical framework that recognizes animals' autonomy, interests and role, for a more nuanced ethical approach and for supporting the best possible research for the benefit animal partakers and wider society.